Minimização do custo do fluxo de escoamento de soja para o porto de Santarém - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2017)
The Santarém Port is situated on the right side of the Tapajós river, near to the confluence of this one with the Amazon river, in the area known as Ponta da Caieira, in the city of Santarém, in the State of Pará. This port is considered with great potential for agricultural production runoff due to its proximity of the Brazilian border with several countries, providing the sending of soybeans on a large scale outwards. However, it is not easy to find a significant amount of research that addresses the issue of soybean in this region, especially in relation to optimizations in the choice of alternative modal flows with low cost. Based on this, a survey was carried out to identify the main soy producing cities, capable of conducting the flow through the port of Santarém, highlighting them as production or attraction centroids in this runoff flow. The methodology used in this study consisted of the application of techniques for Linear Programming (PL) problems, in order to optimize the path travelled by soybean production, from the north of the state of Mato Grosso and Rondônia, to the port of Santarém, using as basis the Minimum Cost Flow Problem (MCFP). The importance of the present work resides in the approach given to the identification of the minimum costs for the displacement of the agricultural load according to the modes and routes currently available and in the future, which also tends to provide the expansion of competitiveness in the transport of the Brazilian agricultural production. The 4-step model was applied to plan the transport and estimate the flow demand between the points of origin and destination of the soybean load. Finally, the results are analysed with the elaboration of scenarios according to the particularities in each transport network, with the objective of identifying the most economically viable routes. Through the results, it was verified that in the second scenario when the soybeans flow performed by the transhipment ports of Porto Velho-RO, ItacoatiaraAM and Teles Pires-MT, it is possible to obtain a reduction in transport operating costs by approximately 27 million reais in relation to the other scenarios analyzed.
Keywords: Porto de Santarém; Soja; Problema de Fluxo de Custo Mínimo; Otimização; Modelo de Quatro Etapas; CNPQ::CIÊNCIAS EXATAS E DA TERRA